Solo Leveling : Volume 9 - Chugong; Chang, Song-nak, 1985-2022; h-goon (Anime creator); Im, Hye-Young; Torres, J., 1969-; Blackman, Abigail; Redice Studio (New York, NY : Ize Press, 2024)
"Jinwoo follows the call of the system and returns to the double dungeon that started it all in the hope of finally receiving some answers. What he doesnt expect is to find his toughest opponent yet! Meanwhile, an S-rank gate looms over Tokyo, and after the loss of their strongest hunters, Japan turns to outside help--but with a worldwide increase in magic beast activity, only one S-rank hunter accepts their offer...Will that be enough to stop the magic beasts before they lay waste to Japan and beyond?"--Amazon
"First published in Korea in 2018 by D&C Webtoon Biz Co., Ltd."--Colophon page
In English, translated from the Korean
Keywords: Hunters -- Comic books, strips, etc; Demonology -- Comic books, strips, etc; Quests (Expeditions) -- Comic books, strips, etc; Magic -- Comic books, strips, etc; Monsters -- Comic books, strips, etc; Graphic novels -- Korea (South); Graphic novels; Fantasy comics; Action and adventure comics; Graphic novel adaptations